Van Helsing the London assignment - Jackman, Hugh.; Bridgeman, Sharon; Universal Pictures (Firm).; Universal Home Entertainment Productions (Firm).; MagnaVision (Firm). (Universal City, Calif. Universal ; distributed in the Philippines by MagnaVision, 2004)
Deep in the heart of London, the sinister creature, Mr. Hyde, terrorizes the late-night streets in a haunting crime spree. With the city in a panic, the Knights of the Holy Order send Van Helsing into London with the mission of tracking down and capturing the evil Mr. Hyde.
Music, John Van Tongeren ; editor, Ken Solomon.
Voices: Hugh Jackman, Robbie Coltrane, David Wenham.
VCD, widescreen presentation; Dolby Digital.
Keywords: Crime -- England -- London -- Drama; Criminal behavior -- Drama